Penambahan Metanol pada Pembuatan Biodiesel dari Minyak Jelantah dengan Katalis Abu Gosok - Zulhardi, Rizky; Restuhadi, Fajar; Zalfiatri, Yelmira (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Biodiesel is an alternative fuel made from vegetable oil or animal fat that can be used as a substitute for diesel fuel. The purpose of the research was to see the effect of methanol addition on biodiesel from used waste cooking oil. The research used a completely randomized design with four treatments which were M1 (methanol 65 ml), M2 (methanol 75 ml), M3 (methanol 85 ml) and M4 (methanol 95 ml) with four replications. The data were analyzed using Analysis of Variance (ANOVA) and continued with duncan’s new multiple range test (DNMRT) at 5% level. The best treatment was M4 with acid number of 0.42 mg KOH/g, total glycerol content of 0.08%, kinematic viscosity of 26.35 cSt, water content of 0,01%, flash point of 227°C, saponification number of 123.46 mg KOH/g and levels of methyl ester 99.4%.Keywords: Biodiesel, waste coocking oil, methanol, ash catalyst